PENGELOLAAN SAMPAH BERWAWASAN LINGKUNGAN DI MADRASAH ALIYAH NEGERI 1 KOTA BEKASI - Octo Iskandar (Abdi Bhara, 2022)
Environmental problems that become a concers inurban areas are regarding waste management, which until nowhas not received a good handling. This is largely due to changesin people's consumption patterns, increasing the volume, type,and characteristics of waste that are increasingly diverse andcontinue to increase every year. The purpose of holding thisactivity is to educate the students in MAN 1 Kota Bekasi so theycould utilize household waste in new products that can be sold sothat it is expected to reduce the risk of environmental pollution.The method used is counseling and interactive discussion,making it easier to deliver and receive extension andsocialization materials. The activity of this program is to explainthe procedures for processing municipal waste into new goods sothat it can become a new business and can bring benefits..